Effect of strain rate and sulfate reducing bacteria on stress corrosion cracking behaviour of X70 pipeline steel in simulated sea mud solution. (June 2019) - Xie, Fei; Wang, Xingfa; Wang, Dan; Wu, Ming; Yu, Chengxiang; Sun, Dongxu
Abstract: In order to reduce the damage to the operation of oil and gas pipelines，the stress corrosion cracking (SCC) behavior of X70 pipeline steel in the South China Sea mud simulation solution under different strain rates and diverse growth days of sulfate-reducing bacteria (SRB) was investigated through slow strain rate test, scanning electron microscopy, and energy-dispersive spectroscopy. Results showed that the sensitivity of SCC initially increased and then decreased with the increase of strain rate when the number of SRB growth days was fixed. When the strain rates were 1 × 10 −6  s −1 and 4 × 10 −6  s −1, greater SRB growth days indicate more sensitivity of the SCC. When the strain rate increased to 7.5 × 10 −6  s −1, the degree of the SCC in metals under the aseptic solution was small, and serious SCC would occur when SRB existed in the environment. The SCC sensitivity was maximum under the synergistic effect of strain rate of 4 × 10 −6  s −1 and SRB number of 5.7 × 10 6  cells/ml. Graphical abstract: Unlabelled Image Highlights: We tested the effects of SRB with different growth days and different strain rates on the SCC of X70 pipeline steel in the South China Sea mud. We found at slower and higher strain rates anodic dissolution controlled the fracture process, while at a medium strain rate the alloy experienced stress corrosion cracking conditions. At the same time, we also found that the X70 pipeline steel SCC in the South China Sea mud is also related to the growth days of SRB. Under the synergistic effect of two conditions, the SCC of pipeline steel is promoted together in this environment.